Discrete element model of the dynamic response of fresh wood stems to impact. (1st August 2016) - Olmedo, I.; Bourrier, F.; Bertrand, D.; Berger, F.; Limam, A.
Highlights: Protection forests maintenance tasks. Forest protection capacity decrease against rockfall. Protection felled tree structures. Structure response under dynamic loading (impact). Discrete element model validation and calibration. Abstract: Forest stands are an efficient natural protection solution against rockfall. After windstorms or forest maintenance tasks, their protection capacity decreases. To compensate the loss of the protective function, a certain number of felled trees can be left on the slope as wooden protective structures. Studies are currently being conducted to estimate the efficiency of these devices and most particularly their resistance to block impacts and their energy dissipation capacity. A numerical model based on the discrete element method is developed herein to describe the fresh wood stem's response to a dynamic loading. The fresh wood stem is modeled by a cylindrical beam composed of discrete elements. Studying the interaction between the elements makes it possible to describe the relation between bending moment and rotation accounting for the elasto-plastic response of the stem. The numerical model is validated by comparing the predictions with analytical solutions. Then the model is calibrated using experimental data from quasi-static and impact laboratory experiments. The numerical approach provides an accurate description of the quasi-static and dynamic response of fresh wood stems. The mechanical properties of fresh wood stems are assessed from the model calibration results and are coherent with the data found in the literature.